Acute high-dose intravenous epoetin did not increase blood pressure in critically ill patients with acute kidney injury - Endre, Zoltan H.; Md Ralib, Azrina; Pickering, John W.; Major, Tamas; Goodkin, David A.; Palmer, Suetonia (American Society of Nephrology., 2011)
Introduction: Erythropoiesis stimulating agents (ESA) correction of renal anemia increases blood pressure in as many as 35% of patients. It is uncertain whether this phenomenon is due to ESA-induced vasoconstriction and/or increased red blood cell mass. The Early Intervention in Acute Renal Failure (EARLYARF) trial4 provided an opportunity to assess whether intravenous (IV) epoetin induces immediate vasoconstriction. Method: A post-hoc analysis of 160 of 163 patients randomized to receive two doses 24 hours apart of IV epoetin (500 U/kg) or placebo. These intensive-care patients were enrolled following identification of acute kidney injury (AKI) by the urinary biomarkers γ-glutamyltranspeptidase and alkaline phosphatase. Hourly mean arterial pressures (MAP), and norepinephrine equivalent dose (NED: determined using equipotency conversion factors for doses of epinephrine, vasopressin, phenylephrine, or dopamine), and hemoglobin (Hb) and hematocrit (Hct) were extracted from clinical records. The differences between maximum and baseline MAP and NED (ΔMAP and ΔNED) were determined at 4, 24, and 72 hours, and Hb and Hct at 7, and 30-day after study drug administration. Result: At baseline, MAP was 78±14 mmHg in the epoetin group and 81±15 mmHg in the placebo group (p=0.22). There were no differences between groups in ΔMAP, ΔNED or ΔMAP adjusted for ΔNED at 4-h after the first and second drug dose (Table 1). Similarly, there were no differences within 24 hours (Figure 1), or at any other time points. Hemoglobin concentration and hematocrit were unchanged. A subgroup analysis of patients with no vasopressor use (n=71) also showed no differences between epoetin and placebo for all outcomes. Conclusion: Parenteral high dose epoetin administration did not acutely increase blood pressure in critically ill individuals at risk of acute kidney injury, suggesting epoetin did not induce acute vasoconstriction.